Isolation and characterization of actinomycetes with in vitro antagonistic activity against Fusarium oxysporum and Meloidogyne incognita from the rhizosphere of rapeseed and mustard: ISOLATION AND CHARACTERIZATION OF ACTINOMYCETES WITH IN VITRO ANTAGONISTIC ACTIVITY - B LAKSHMI SOWJANYA,; K SANKARI MEENA,; Bh SARVANI,; A VIJAYA GOPAL,; M SANTHA LAKSHMI PRASAD, (Journal of Oilseeds Research, 2023)
Twelve isolates of actinomycetes were isolated from soilsamples collected from the rhizosphere of organically cultivated mustard and rapeseed in Sikkim, India. The isolates were morphologically distinguished for their shape and colour and microscopically characterized using Gram staining. The effective 10 Gram-positive actinomycetes isolates were examined for their bio-control efficacy against Meloidogyne incognita and Fusarium oxysporum in vitro. The isolates were studied for biochemical and molecular characterization using 16s rRNA sequencing. The effective isolate (AC-S-2) from the in vitro and biochemical studies was designated as Streptomyces hydrogenans.